2020
DOI: 10.1038/s41533-020-0182-2
|View full text |Cite
|
Sign up to set email alerts
|

Bringing asthma care into the twenty-first century

Abstract: Despite access to diagnostic tests and effective therapies, asthma often remains misdiagnosed and/or poorly controlled or uncontrolled. In this review, we address the key issues of asthma diagnosis and management, recent evidence for levels of asthma control, the consequences of poor control and, in line with that, explore the potential reasons for poor asthma control and acute exacerbations. Based on recent evidence and current guidelines, we also aim to provide practical answers to the key questions of how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 101 publications
(168 reference statements)
0
25
0
1
Order By: Relevance
“…It has been demonstrated that the recognition of various stimuli and the associated inflammatory responses are important in the development and exacerbation of asthma (6,7). Corticosteroids, b2 agonists and leukotriene receptor antagonists are commonly used in the treatment of asthma (8). Side effects, including respiratory tract infections and decreased bone density, often occur with the use of inhaled corticosteroids, which are primary medications in all steps of asthma therapy (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the recognition of various stimuli and the associated inflammatory responses are important in the development and exacerbation of asthma (6,7). Corticosteroids, b2 agonists and leukotriene receptor antagonists are commonly used in the treatment of asthma (8). Side effects, including respiratory tract infections and decreased bone density, often occur with the use of inhaled corticosteroids, which are primary medications in all steps of asthma therapy (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…12 The second parameter is improving education of both providers and patients. This may be accomplished by a variety of strategies 19 including participating in global efforts such as GINA. [6][7][8][9] And finally, there is a need to increase the availability of assessment tools.…”
Section: Recommendationsmentioning
confidence: 99%
“…Referral to a specialist is appropriate when a primary care patient’s long-term condition worsens suddenly, or when a patient fails to respond to the standard GINA step care management (Fig. 1 ) or has poor asthma control despite showing good adherence and the correct inhalation technique [ 22 ].…”
Section: Analysis Of An Exacerbationmentioning
confidence: 99%